Review, Estimation and Analysis of Agricultural Subsidies in Mongolia - Grunjal, Kisan; Annor-Frempong, Charles (World Bank, Washington, DC, 2015)
With global food crises and food price volatility in recent years, agricultural subsidies have once again gained prominence as a policy instrument in many developing countries. In Mongolia too, subsidies to the agriculture sector mainly through government budgetary transfers, have increased over time. These gained prominence in 2008 when a global, regional (the drought in Russia, and Kazakhstan, the two main suppliers to Mongolia), and the national food production shortfall sent domestic wheat prices soaring to record levels. Wheat production had reached an all-time low during the years 2005 to 2007. Consequently, subsidies to crop, livestock, and agroprocessing sectors have increased since 2008, and now represent a complex set of programs, sometimes with conflicting and overlapping goals and intended beneficiaries.